Improved and simpler estimation of scale linearity contribution to topography measurement - Giusca, Claudiu L.; Goel, Saurav (Elsevier, 2019)
Instruments measuring surface topography with nanometre accuracy are essential tools for studying nanotechnology. Despite their maturity, erroneous observations due to various error sources are widespread, particularly due to calibration and traceability issues. The current method of vertical scale calibration (which is one of the error sources), relies on the depth standard method that limits the traceability of the instrument to the calibrated range determined by the minimum and maximum discrete values. This paper reports a new method relying on the tilted flat that was aimed at mapping the linearity deviations continuously within the range covered by the tilt angle. The full traceability in this case requires only the measurement of a single depth measuring standard, that can be optimally selected to achieve least uncertainty associated with the amplification coefficient of the scale. The proposed method opens the opportunity for high dynamic range calibration, currently unachievable with conventional calibration techniques.